NDVI assessment versus two impact factors analysis (separate analysis based on chlorophyll content and leaf cellular structure): which method is more effective to detect declining health of an individual tree? - K. N. Au (Geocarto International, 2023)
In detecting the internal health of an individual tree, “two impact factors analysis” refers to evaluation of NIR and RED separately, instead of merging them together in one formula as in NDVI assessment. We use high resolution WorldView-2/-3 satellite data for our study. From our global case studies of stressed trees, we have found the following results: (1) NDVI works when the spectral reflectance in both NIR and RED bands deteriorates together/concurrently. (2) NDVI does not work when the spectral reflectance in NIR and RED bands varies. This will happen, as shown by our case studies of Tree 1 and Tree 2 of the removed stressed trees, and Tree 4 and Tree 5 of the collapsed stressed trees.